Chasing informality: Evidence from increasing enforcement in large firms in Peru - Mariano Bosch Mossi; Stephanie González; Maria Teresa Silva- Porto (Inter-American Development Bank (IDB), 2021)
Evasion of labor market regulations in middle income countries is systemic. This is generally known as informality. In Latin America, where less than 50% of workers are registered with social security, this is a permanent phenomenon and encompasses a variety of economic realities ranging from subsistence self-employment to evasion of certain regulations including social security contributions. In this study we analyze the role of enforcement in curbing informality in large formal firms in Peru, where informality levels are around 70%. Through the Peruvian National Labor Control Superintendence (SUNAFIL) we randomly sent 697 letters to formal Peruvian firms of more than 50 workers, indicating their obligation to enroll workers in social insurance systems (health and pensions). Two types of letters were sent, one with a deterrence message and one emphasizing the benefits of formalization. One year after the letters were sent, we found a positive and statistically significant effect on the number of workers enrolled in social security (9.8% on average). Only strict deterrence messages had a significant impact, and only in very large firms. This evidence suggests that there is room for improvement in compliance with labor regulations through more proactive monitoring and behavioral tools such as reminders, but effects could be concentrated in the largest firms.
Keywords: C93; D91; H55; J46; O17; 330; Randomized Controlled Trial; Social Security; Audit; Letters; Informality; Labor formalization